Development of the Object-Oriented Dynamic Simulation Models Using Visual C++ Freeware. (16th March 2016) - Kozynchenko, Alexander I.; Kozynchenko, Sergey A.
Abstract : The paper mostly focuses on the methodological and programming aspects of developing a versatile desktop framework to provide the available basis for the high-performance simulation of dynamical models of different kinds and for diverse applications. So the paper gives some basic structure for creating a dynamical simulation model in C++ which is built on the Win32 platform with an interactive multiwindow interface and uses the lightweight Visual C++ Express as a free integrated development environment. The resultant simulation framework could be a more acceptable alternative to other solutions developed on the basis of commercial tools like Borland C++ or Visual C++ Professional, not to mention the domain specific languages and more specialized ready-made software such as Matlab, Simulink, and Modelica. This approach seems to be justified in the case of complex research object-oriented dynamical models having nonstandard structure, relationships, algorithms, and solvers, as it allows developing solutions of high flexibility. The essence of the model framework is shown using a case study of simulation of moving charged particles in the electrostatic field. The simulation model possesses the necessary visualization and control features such as an interactive input, real time graphical and text output, start, stop, and rate control.